Japan's China Policy - Hagström, Linus (European Institute of Japanese Studies East Asian Economics and Business Series, 2005)
Japan's China Policy understands Japan's foreign policy in terms of power - one of the most central concepts of political analysis. It contributes a fresh understanding to the subject by developing relational power as an analytical framework and by applying it to significant issues in Japan's China policy: the negotiations for a bilateral investment protection treaty and the disputed Pinnacle (Senkaku/Diaoyu) Islands. Hagström demonstrates that Japan exerted power over China in such divergent empirical settings for the most part by using civilian instruments positively, defensively and through non-action. Given that Japan's foreign policy is often portrayed rather enigmatically in terms of power, the unique contribution of Japan's China Policy is to demonstrate how to analyze power aspects of Japan's foreign policy in a more coherent fashion. This revealing approach to Japan's foreign policy will be of huge interest to anyone